Modeling and Analysis of Multi-time Scale Transient Characteristics of a Series Hybrid Power System - Ying, Zhang; Xuhui, Wen; Hongyang, Li; Ke, Li; Lin, Wei Jia; Youlong, Wang (International Conference on Electrical Machines and Systems (Online), 2019)
In this paper, modeling and analysis of multi-time scale transient characteristics of a series hybrid power system are presented. The electromechanical coupling system composed of diesel engine, generator and composite power has many different transient time scales, which brings difficulties to the optimization of simulation efficiency. Therefore, implicit trapezoid integral algorithm is applied to analysis transient characteristic of the hybrid power system, and adaptive variable-step algorithm is used for dynamic process. Not only to meet the simulation accuracy and minimize simulation time, but also to reflect the interaction between electrical and mechanical process, a switch flow-graph model (SFGM) is introduced. Finally, the effectiveness and superiority of the proposed method is verified through simulation results.